The terrible threes - Reed, Ishmael 1938- (Atheneum, 1989)
"The White House is implicated in a plot to rid America of its surplus people and the Third World of its nuclear weapons."
Keywords: Politik; USA; United States -- Politics and government -- Fiction; Political fiction; Satire